The Role of the Capital Market in the Indonesian Economy - Fitriyanti, Fadia; Gultom, Qinnara Zegia; Ulya, Sauva Nadhivatul (Global Sustainability Research Institute, 2026)
The capital market has evolved into a major source of corporate financing and is no longer perceived merely as an alternative to bank-based funding. Through various corporate actions such as initial public offerings, rights issues, bond issuance, derivatives, and mutual funds, the capital market offers more efficient and flexible financing mechanisms, particularly in periods of rising inflation and increasing loan interest rates. Under such conditions, reliance on bank credit becomes less attractive due to higher financing costs, thereby strengthening the strategic role of the capital market in supporting business sustainability and expansion. In the Indonesian context, the capital market plays a crucial role in mobilizing long-term funds that contribute to national economic growth. Although capital market performance experiences annual fluctuations influenced by domestic macroeconomic conditions and global economic dynamics, corporate interest in utilizing capital market instruments remains consistently high. This is largely due to the capital market’s capacity to provide substantial funding volumes, enhance corporate liquidity, and improve capital structure efficiency. Moreover, the development of the sharia capital market further strengthens financial system inclusivity by offering investment instruments that comply with Islamic principles. Institutions such as the Indonesia Stock Exchange facilitate both conventional and sharia-compliant instruments, enabling broader participation from investors and issuers.